Classification of Mindfulness Meditation and Its Impact on Neural Measures in the Clinical Population - Ngan, Sze Ting Joanna; Cheng, Pak Wing Calvin (Frontiers in Psychology, 2022)
Different forms of mindfulness meditation are increasingly integrated in the clinical practice in the last three decades. Previous literatures have identified changes in the neurophysiology and neurochemistry of the brain resulting from different mindfulness meditation practices to the general population. However, research on neural correlates of different types of meditation particularly on the clinical outcomes is still very sparse. Therefore, the aim of this article is to review the neural impact of mindfulness meditation interventions on different mental disorders via the classification of main components of mindfulness meditation. The clearer classification of mindfulness meditation may inform future clinical practice and research directions.